Longitudinal Relations between Sectarian and non-Sectarian Community Violence and Child Adjustment in Northern Ireland - Cummings, E. Mark (Dev Psychopathol, 2013)
Although relations between political violence and child adjustment are well-documented, long-term longitudinal research is needed to adequately address the many questions remaining about the contexts and developmental trajectories underlying the effects on children in areas of political violence. The present study examined relations between sectarian and non-sectarian community violence and adolescent adjustment problems over four consecutive years for mother-child dyads (total N = 1015, 485 boys, 517 girls) living in socially deprived neighborhoods in a context of historical and ongoing political violence, that is, Belfast, Northern Ireland. Both sectarian and non-sectarian community violence predicted youth adjustment across four years, consistent with the hypothesis that both of these elements of the social ecology merit consideration with regard to children's well-being in contexts of political violence. The impact of sectarian community violence on adolescent adjustment was further accentuated in neighborhoods characterized by higher crime rates. Discussion considers the implications for evaluating social ecologies pertinent to the impact of political violence on children.